IEEE INFOCOM 2020 - IEEE Conference on Computer Communications 2020
DOI: 10.1109/infocom41043.2020.9155490
|View full text |Cite
|
Sign up to set email alerts
|

Joint Access Point Placement and Power-Channel-Resource-Unit Assignment for 802.11ax-Based Dense WiFi with QoS Requirements

Abstract: If it is the author's pre-published version, changes introduced as a result of publishing processes such as copy-editing and formatting may not be reflected in this document. For a definitive version of this work, please refer to the published version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Rational planning (i.e., minimizing the number of APs) and effective planning of the wireless network (i.e., maximizing the throughput) for indoor/outdoor operation usually requires the consecutive evaluation of many candidate solutions using optimization algorithms. Among the optimization algorithms commonly used in network planning, we can mention: e.g., heuristics [12,[22][23][24], GA [25][26][27][28], or Particle Swarm Optimization (PSO) [29][30][31].…”
Section: Network Planning Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rational planning (i.e., minimizing the number of APs) and effective planning of the wireless network (i.e., maximizing the throughput) for indoor/outdoor operation usually requires the consecutive evaluation of many candidate solutions using optimization algorithms. Among the optimization algorithms commonly used in network planning, we can mention: e.g., heuristics [12,[22][23][24], GA [25][26][27][28], or Particle Swarm Optimization (PSO) [29][30][31].…”
Section: Network Planning Algorithmsmentioning
confidence: 99%
“…Once the coverage requirement is met, it is investigated if any two closely spaced access points can be replaced by one. In [24], the authors designed an 802.11ax-based dense Wi-Fi network to provide service to a large number of users minimizing the number of APs and fulfilling the users' throughput requirement. The authors designed a heuristic algorithm with polynomial time complexity and compared the performance to the random and Greedy solution.…”
Section: Network Planning Algorithmsmentioning
confidence: 99%
“…Concurrently, [15] established that adapting TX PWR can lead to increased throughput and reduced energy consumption. More recently, in 2020, [18] casts the issues of positioning the APs of a WLAN and choosing their TX PWR as an optimization problem. The authors provides a solution to this problem that delivers a static configuration of TX PWR for a WLAN.…”
Section: Related Workmentioning
confidence: 99%
“…With a well-designed WLAN, interference can be mitigated. Many research works focused on the planning and design phases to avoid co-channel interference in the WLAN systems [1][2][3][4][5]. However, even with a well-designed WLAN, some issues are exacerbated such as interference and growth in network size from new nodes being introduced into the system exacerbated.…”
Section: Preliminary Studymentioning
confidence: 99%
“…In [2], GA was adopted to provide a cost-effective WLAN in terms of coverage and capacity under budget constraints. In [5], both channel selection and the QoS of WLAN requirements were jointly optimized, while the authors in [4] suggested using GA to consider additional metrics such as capacity, cost, coverage, and interference. Apart from node placement optimization, GA in WLAN design can also be included in the design of patch antennas [12,13] as well as the handover process between Wi-Fi and LTE in the unlicensed spectrum, as described in [14].…”
Section: Preliminary Studymentioning
confidence: 99%